Pollution: the population explosion - Jones, Claire; Gadler, Steve J.; Engstrom, Paul H (J.M. Dent & Sons Ltd. : London ; E.P. Dutton & Co. Inc. : New York, 1972)
Discusses the psychological and physical effects of continued population growth and presents some of the proposed solutions to this problem.
Keywords: Population -- Juvenile literature; Food supply -- Juvenile literature